2020
DOI: 10.1007/s00167-020-05863-3
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime revision risk for medial unicompartmental knee replacement is lower than expected

Abstract: Purpose Unicompartmental knee replacement (UKR) is widely considered to be a pre-total knee replacement (TKR) particularly in the young. The implication of this is that it is sensible to do a UKR, even though it will be revised at some stage, as it will delay the need for a TKR. The chance of a UKR being revised during a patient's life time has not previously been calculated. The aim of this study was to estimate this lifetime revision risks for patients of different ages undergoing UKR. Methods Calculations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Our estimates were double that from a recent study. Kennedy et al 30 reported lower lifetime risk of revision for UKA across all age groups (15% at 55 years to 3.7% at 85 years), although these were based on national population-based statistics. Our dataset was linked directly to individual patient mortality data and may therefore reflect a more accurate mortality profile specific to UKA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our estimates were double that from a recent study. Kennedy et al 30 reported lower lifetime risk of revision for UKA across all age groups (15% at 55 years to 3.7% at 85 years), although these were based on national population-based statistics. Our dataset was linked directly to individual patient mortality data and may therefore reflect a more accurate mortality profile specific to UKA patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 UKA is often performed as a conservative treatment for younger patients, 32 with lower incidence of infections, compared with TKA-TKA revision. 18,30,32 It is important to note, however, that TKA conversion of a failed UKA has inferior outcomes to primary TKA, therefore lifetime risk of revision estimates may be informative when deciding between the two procedures for a specific patient. 34 Females have a higher lifetime risk of revision for UKA compared with males, in contrast to TKA where males have a higher lifetime risk of revision.…”
Section: Discussionmentioning
confidence: 99%
“…Intense and regular athletic activity may lead to an increase in stress on the implant–bone interface, causing an acceleration in wear and, therefore, can lead to higher revision rates in young and active patients after total joint replacement [ 17 , 32 ]. As the patients who are suitable for implantation of UKR tend to be younger and more active than those suitable for implantation of TKR and the fact that lifetime risk of revision surgery in UKR is higher with younger age at surgery [ 33 ], surgeons encourage patients to engage in low-impact activities such as cycling and swimming. However, there is no study reporting on the relationship between use and wear in UKR [ 10 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…9-14 The majority of these studies have made assumptions of life expectancy based upon mortality rates from the general population. 9-11 However, patients undergoing primary KA may have different mortality rates compared to the general population. 15 Therefore, estimates using general population mortality rates may underestimate the risk of revision in patients undergoing primary KA, especially in younger patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Previous authors have sought to estimate the lifetime risk of revision KA. [9][10][11][12][13][14] The majority of Health Scotland (PHS) performs data-linkage by using a unique identifier assigned to every patient in Scotland from birth -the community health index (CHI) number. The completeness of the SMR01 datasets is subject to annual audit and the Information Services Division of PHS undertakes quality assessments of all SMR01 data every four years.…”
Section: Introductionmentioning
confidence: 99%